A Concept Analysis of Self-Management of Cancer Pain - Masako Yamanaka (Elsevier, 2018)
The objective of the study was to conduct a concept analysis of "self-management of cancer pain" to develop a theoretical definition of the concept and identify its attributes, antecedents, and outcomes. The Rodgers' evolutionary model of concept analysis was used. Literature published from January 2000 to February 2017 containing the terms, "cancer pain" and "self-management" in their title and/or abstract was assessed. Twenty-seven studies were selected for this analysis. Self-management of cancer pain is defined as "the process in which patients with cancer pain make the decision to manage their pain, enhance their self-efficacy by solving problems caused by pain, and incorporate pain-relieving strategies into daily life, through interactions with health-care professionals." The attributes of self-management of cancer pain were classified into the following five categories: Interaction with health-care professionals, decision-making to pain management, process for solving pain-related problems, self-efficacy, and incorporating strategies for pain relief into daily life. The antecedents were classified into the following seven categories: Physical functions, cognitive abilities, motivation, undergoing treatment for pain, receiving individual education, receiving family and health-care professionals' support, and health literacy. The outcomes were classified into the following three categories: pain relief, well-being, and empowerment. The attributes of self-management of cancer pain can be used as components of nursing practice to promote patient self-management of cancer pain. The categories of antecedents can be used as indicators for nursing assessment, and the outcomes can be used as indicators for evaluations of nursing intervention.